Physiological basis for yield differences in maize (Zea mays L.) under varying nitrogen rates and planting windows in the savannas of Nigeria - Ahmad, N.M. (Bayero University Kano, 2024)
Maize Production in the savannas of West and Central Africa (WCA) is limited by intermittent drought during cropping season and low soil fertility which affects its productivity and the overall livelihood of smallholder farmers. This study aimed to determine the physiological basis of differential yield response of some maize varieties under varying level of nitrogen and different sowing windows in Guinea and Sudan savannas of Nigeria and identify stress surrogate traits for yield improvement in maize. Field experiments were conducted at Bayero University, Kano (11058`38.63892N, 80 25`7.01868E), altitude 451m above sea level in the Sudan savanna and Zaria (11.16050610N, 7.64535890E) in Northern Guinea Savanna. Treatments consisted of three sowing windows at two weeks intervals, two levels of nitrogen (30 and 100 Kgha-1) and four improved maize varieties (SAMMAZ15, SAMMAZ 16, SAMMAZ 40 and SAMMAZ 51). These were laid out in a Split-split plot design with three replications. Sowing window was allocated to the main plot, varieties to the sub plot and Nitrogen to the sub-sub plot. The results indicated that the most favorable sowing window identified for planting of maize is the mid-June to late June for Sudan Savanna and mid-June to early July for Northern Guinea Savanna. Furthermore, the choice of maize variety emerges as a critical factor influencing yield, irrespective of location. SAMMAZ 40 and SAMMAZ 51 varieties demonstrated superior performance in terms of both yield (3,814 kg/ha and 3,873 kg/ha, respectively) and biomass accumulation at both study locations. Additionally, while higher nitrogen application rates contribute to increased biomass, this effect is contingent on the interplay between planting period and variety selection, highlighting their combined influence on maize yield in terms of both quantity and weight. In instances of low nitrogen, specific surrogate traits such as leaf area index for grain yield, Intercepted photosynthetic active radiation for harvest index, and electrical conductivity, total dissolve salt, chlorophyll content, and leaf area index for hundred seed weight were identified as key indicators.